Acute chlorfenapyr toxicity in 3 dogs from a single household. Issue 6 (21st October 2019) - Davy, Rachel B.; Campos, Samantha; Lynch, Alex M.
Abstract: Objective: To describe the clinical characteristics of acute chlorfenapyr toxicity in 3 dogs from a single household. Case Summary: A 4‐year‐old neutered female Labrador Retriever was presented with severe hyperthermia (42.6°C [108.6°F]). Emergency management consisting of fluid resuscitation, active cooling, general anesthesia, gastric lavage, activated charcoal administration, and intravenous lipid emulsion was started immediately on the suspicion of toxin exposure. The dog developed symptoms following peracute death in 2 other small breed dog housemates. All dogs had a rapid onset of gastrointestinal signs, neurologic signs, and panting. The dog made a rapid and complete recovery and was discharged 48 hours later. Examination of gastric contents collected from the deceased dogs identified the presence of chlorfenapyr. New or Unique Information Provided: This is the first reported case of chlorfenapyr toxicity in dogs. Previous case reports in human medicine have reported a variable mortality rate, although 1 of 3 dogs described here made a complete recovery. Chlorfenapyr should be considered in cases of suspected toxicity with similar presenting signs.